"Tears on a Mask": In the Time of Covid-19. Issue 1 (26th December 2022) - Evans, Louise
"Analysing digital poetry, namely poetry published and disseminated via social media, will allow for a better chance at understanding how literature participates in contemporary culture" (Schaefer 179 ). Contemporary culture is now marked by the Covid-19 global pandemic. As daily lives are permeated by various governmental restrictions and lockdowns that prevent physicality and privilege digitality, online operations have never been more necessary for communication, connection, and interaction. Meanwhile, a new generation of Spanish poets wields the social media environment as its writing space. Instagram poems or Instapoemas published by the likes of Leticia Sala, Elvira Sastre, and Diego Bergasa exemplify personal experience and grapple with nostalgia for "pre-Covid" life. These texts not only forge connections between reader–users in a period of isolation and uncertainty but assist in navigating the changing society of today, reflecting on the past while posing questions regarding the future of society and of contemporary poetry.